Rising gastrointestinal malignancies in North India: a comprehensive review - Tali, Tavseef Ahmad; Bashir, Mustafa; Ashraf, Bilkees; Teli, Toufeeq Ahmed; Amin, Fiza (International Journal of Research in Medical Sciences, 2025)
Gastrointestinal (GI) malignancies, including cancers of the esophagus, stomach, colorectal region, gallbladder and liver, pose a significant public health challenge in North India, with rising incidence driven by unique regional factors. This comprehensive review synthesizes current literature to analyze the epidemiology, risk factors, clinical characteristics and management challenges of GI cancers in North India. Esophageal cancer, predominantly squamous cell carcinoma, exhibits high incidence in areas like Mizoram, while gastric cancer is prevalent in the Kashmir Valley. Colorectal cancer is increasing due to urbanization and lifestyle changes and gallbladder cancer is a major concern in the Ganges River belt. Liver cancer, primarily hepatocellular carcinoma, is linked to chronic hepatitis infections. Key risk factors include dietary habits (e.g., smoked meats, high-fat diets), tobacco use, Helicobacter pylori infection, hepatitis B and C and environmental carcinogens. Advanced-stage diagnosis, limited access to diagnostic tools and inadequate region-specific research hinder effective management. Preventive strategies, such as H. pylori eradication, hepatitis B vaccination and lifestyle modifications, alongside enhanced screening and genomic research, are critical for reducing the burden. This review underscores the need for collaborative efforts to improve early detection, treatment access and region-specific guidelines to address this growing epidemic.